Mapping the circumnuclear regions of the Circinus galaxy with the Imaging X-ray Polarimetry Explorer. Issue 1 (9th November 2022) - Ursini, F; Marinucci, A; Matt, G; Bianchi, S; Marin, F; Marshall, H L; Middei, R; Poutanen, J; Rogantini, D; De Rosa, A; Di Gesu, L; García, J A; et al.
ABSTRACT: We report on the Imaging X-ray Polarimetry Explorer ( IXPE ) observation of the closest and X-ray brightest Compton-thick active galactic nucleus (AGN), the Circinus galaxy. We find the source to be significantly polarized in the 2–6 keV band. From previous studies, the X-ray spectrum is known to be dominated by reflection components, both neutral (torus) and ionized (ionization cones). Our analysis indicates that the polarization degree is 28 ± 7 per cent (at 68 per cent confidence level) for the neutral reflector, with a polarization angle of 18° ± 5°, roughly perpendicular to the radio jet. The polarization of the ionized reflection is unconstrained. A comparison with Monte Carlo simulations of the polarization expected from the torus shows that the neutral reflector is consistent with being an equatorial torus with a half-opening angle of 45°–55°. This is the first X-ray polarization detection in a Seyfert galaxy, demonstrating the power of X-ray polarimetry in probing the geometry of the circumnuclear regions of AGNs, and confirming the basic predictions of standard Unification Models.